Political Myth and Achebe’s Arrow of God (Journal of Science and Technology, 2016)
Many African states are in dire political distress. During the political struggle for freedom and the immediate aftermath of political independence, leaders were able to mobilize the citizenry on the banner of the myth of the common nation state, a veritable paradise on earth. The stark reality now is that a combination of factors has led to general disillusionment. One of the ways to rekindle mass political enthusiasm is for the political elite to fashion new myths of the state which the general populace can identify with. This paper suggests that modern leaders of Africa can learn valuable lessons from Achebe’s Arrow of God. Firstly, when a nation is in a crisis, a new political myth becomes necessary. This new myth should be consciously crafted by experts brought together by political leaders. Secondly, if leaders fail to give the state a new cohesive myth, the nation may disintegrate into tribal enclaves, or even worse, any passionate fringe group will fashion a political myth – positive or negative – for the state. The paper concludes that political leaders in Africa should set the process in motion to deliberately craft new political myths for the various countries.